Physiological behavior during stress anticipation across different chronic stress exposure adaptive models. (2nd January 2022) - Popovic, Dejana; Damjanovic, Svetozar; Popovic, Bojana; Kocijancic, Aleksandar; Labudović, Dragana; Seman, Stefan; Stojiljković, Stanimir; Tesic, Milorad; Arena, Ross; Lasica, Ratko
Abstract: Anticipation of stress induces physiological, behavioral and cognitive adjustments that are required for an appropriate response to the upcoming situation. Additional research examining the response of cardiopulmonary parameters and stress hormones during anticipation of stress in different chronic stress adaptive models is needed. As an addition to our previous research, a total of 57 subjects (16 elite male wrestlers, 21 water polo player and 20 sedentary subjects matched for age) were analyzed. Cardiopulmonary exercise testing (CPET) on a treadmill was used as the laboratory stress model; peak oxygen consumption (VO2 ) was obtained during CPET. Plasma levels of adrenocorticotropic hormone (ACTH), cortisol, alpha-melanocyte stimulating hormone (alpha-MSH) and N-terminal-pro-B type natriuretic peptide (NT-pro-BNP) were measured by radioimmunometric, radioimmunoassay and immunoassay sandwich technique, respectively, together with cardiopulmonary measurements, 10 minutes pre-CPET and at the initiation of CPET. The response of diastolic blood pressure and heart rate was different between groups during stress anticipation ( p  = 0.019, 0.049, respectively), while systolic blood pressure, peak VO2 and carbon-dioxide production responses were similar. ACTH and cortisol increased during the experimental condition, NT-pro-BNP decreased and alpha-MSH remained unchanged. All groups had similar hormonal responses during stress anticipation with the exception of the ACTH/cortisol ratio. In all three groups, ΔNT-pro-BNP during stress anticipation was the best independent predictor of peak VO2 (B = 36.01, r  = 0.37, p  = 0.001). In conclusion, the type of chronic stress exposure influences the hemodynamic response during anticipation of physical stress and the path of hormonal stress axis activation. Stress hormones released during stress anticipation may hold predictive value for overall cardiopulmonary performance during the stress condition. LAY SUMMARY: The study revealed differences in hormonal and hemodynamic responses during anticipation of stress between athletes and sedentary participants. Stress hormones released during stress anticipation may hold predictive value for overall cardiopulmonary performance during the stress condition.